First record of South American leaf miner, Tuta absoluta (Meyrick, 1917) from Jammu, India - SHARIEF, SEHROSE; SHANKAR, UMA; MUKHTAR, YOUSRA (The Indian Journal of Agricultural Sciences, 2024)
Tomato leaf miner, Tuta absoluta (Meyrick, 1917), is an invasive insect pest that was introduced to India from South America wherein its initial occurrence in India was recorded in tomato fields of Pune, Maharashtra in October 2014. However, it was first observed in Northern India in 2016, with no prior reports from Jammu region until 2022. This article documents the first recorded instance of T. absoluta infestation on tomatoes in Jammu region. The survey was conducted for two consecutive years (2022 and 2023) during the tomato cropping period (March-June), encompassing four different districts of Jammu regions viz., Udhampur, Doda, Ramban and Jammu. This research provides valuable insights into spread and impact of T. absoluta in the Jammu region. The consolidated picture of two-year data revealed highest leaf and fruit infestation in district Udhampur, followed by Doda and Jammu districts, respectively. Curiously, there were no records of T. absoluta infestations in Ramban district. To gain a better understanding of biology and morphometrics of this pest, larvae were collected and reared in the laboratory of Division of Entomology, SKUAST-Jammu. The crucial data on biological and morphometric attributes were collected which can facilitate further investigations and development of potential management strategies.